Phytochemical constituents and pharmacological activities of calotropis procera - Qureshi, Absar A.; Qureshi, Azfar A.; Omer, Shaista; Sanghai, Dhirendra B.; Setty, S. R.; Bhajipale, N. S. (Plant Archives, 2008)
In spite of many synthetic compounds, the most efficient drugs have their origin directly or indirectly related with the plant kingdom. Many of the plant extracts have proven to posses important pharmacological actions depending upon the chemical constituents present. Calotropis procera, plant generally considered as a poisonous whereas widely used in the traditional medicinal system like Ayurveda and Unani. This plant has been reported to poses alkaloids, glycosides, flavonoids, triterpines etc in different parts and exhibit various pharmacological activities like anti-fertility, wound healing, antimalerial, antidiarrhoeal, anti-inflammatory etc. This review highlights some of the phytochemical and pharmacological aspects of Calotropis procera.
Keywords: calactin; calotoxin; Calotropis procera; pharmacological activities; phytochemical constituents; procesterol